Low‐level viraemia as a risk factor for virologic failure in children and adolescents living with HIV on antiretroviral therapy in Tanzania: a multicentre, retrospective cohort study - Kevin P. McKenzie; Duc T. Nguyen; Lilian B. Komba; Eunice W. Ketang'enyi; Neema E. Kipiki; Evance N. Mgeyi; Lumumba F. Mwita (Journal of the International AIDS Society)
Abstract Introduction Viral load (VL) of 1000 copies/ml or greater is commonly used to define virologic failure (VF) in children and adolescents living with HIV (CALHIV) in low‐ and middle‐income countries (LMICs). However, evidence in adults suggests that low‐level viraemia (LLV) (VL 50–999 copies/ml) increases the risk of subsequent VF. There is limited research on LLV in CALHIV. Methods This study retrospectively reviewed VL data from Baylor College of Medicine Children's Foundation—Tanzania (sites in Mbeya and Mwanza) collected between January 2015 and December 2022. CALHIV (0−19 years) on antiretroviral therapy for ≥6 months with at least one VL <50 copies/ml plus ≥2 subsequent VLs were included. VF was defined as both VL ≥1000 and ≥200 copies/ml. Multivariable Cox regression models were used to assess the association between LLV and VF, reporting adjusted hazard ratios (aHR) with 95% confidence intervals (CI). Results Among 2618 CALHIV included in the outcome analysis (median age 13.2 years, 52.5% female), 81.9% were on first‐line dolutegravir‐based regimens and LLV was found in 40.5%. CALHIV with LLV had an increased risk of VF with aHRs of 1.63 (CI 1.38−1.91) (VL ≥1000 copies/ml) and 3.85 (3.33, 4.46) (VL ≥200 copies/ml). When stratifying by LLV (50−199, 200–399 and 400–999 copies/ml), all levels were associated with increased risk for VF (VL ≥1000 copies/ml) with aHRs of 1.39 (1.13, 1.69), 1.69 (1.33, 2.16) and 2.03 (1.63, 2.53). When VF was defined as VL ≥200 copies/ml, the corresponding aHRs were 1.41 (1.15, 1.72), 7.99 (6.68, 9.57) and 9.37 (7.85, 11.18). Conclusions LLV is associated with a greater risk of VF in CALHIV. The risk of VF increases with higher levels of LLV. This study provides further evidence for revising guidelines in LMICs that define VF as VL ≥1000 copies/ml.